Hepatitis E virus genotypes and subgenotypes causing acute hepatitis, Bulgaria, 2013-2015. - Roberto Bruni; Umbertina Villano; Michele Equestre; Paola Chionne; Elisabetta Madonna; Dilyana Trandeva-Bankova; Maria Peleva-Pishmisheva; Tencho Tenev; Eleonora Cella; Massimo Ciccozzi; Giulio Pisani; Elitsa Golkocheva-Markova; et al. (PLoS ONE, 2018)
Background In industrialized areas of the world, including Europe, Hepatitis E Virus (HEV) is considered an emerging pathogen. In fact, autochthonous cases caused by HEV genotype 3 (HEV-3) are increasingly reported. Several studies described the human HEV-3 subtypes and strains circulating in West Europe countries; in contrast, very little is known about the HEV strains responsible for acute hepatitis E in countries of East Europe/Balkans, such as Bulgaria. Methods and findings Anti-HEV IgM positive serum samples (n = 103) from acute hepatitis cases (2013-2015) from all over Bulgaria were analysed for HEV RNA by Real-Time PCR. Viremia was detected in 90/103 samples. A fragment of the viral genome (ORF-2 region) was amplified by nested PCR from 76/90 viremic samples, leading to a sequence in 64 of them. Genotyping by phylogenetic analysis with standard reference sequences showed HEV-1 in 1/64 cases, HEV-3 in 63/64. Subtyping of HEV-3 sequences showed 3e (39/63, 62%), 3f (n = 15/63, 24%) and 3c (n = 8/63, 13%) subtypes; in one case the sequence subtype was uncertain and classified as 3hi. In the phylogenetic tree, most 3e sequences grouped in two well distinct clusters (A and B), each one with very low intragroup genetic distances. In contrast, 3f and 3c were interspersed with reference sequences and showed lower tendency to cluster and/or higher intragroup distances. Geographically, while 3f and 3c were scattered throughout the country, 3e was restricted to the South-West area, with most cases in two towns about 40 kilometres apart from each other. Conclusions Most acute hepatitis E cases in Bulgaria are caused by HEV-3, subtypes 3e, 3f and 3c. Circulation of 3e appears quite different from 3f and 3c, with 3e restricted to the South-West area while 3f and 3c diffused over the country. The factors underlying the observed molecular and geographical differences remain to be investigated.